Life Cycle Assessment of Dairy Buffalo Calves in an Italian Farm - Sabia, Emilio; Napolitano, Fabio; Rosa, Giuseppe De; Gauly, Matthias; Braghieri, Ada; Pacelli, Corrado (Journal of Buffalo Science, 2018)
The aim of this paper was to examine the environmental consequences of raising buffalo calves, as assessed by life cycle assessment. Life cycle assessment has been widely used to assess the environmental impact of different livestock production systems. The primary data were collected from 32 animals aged 0-90 days. Calves were allowed to uptake colostrum before separation from their mothers within 24-h after birth. After separation, the animals were kept individually (1 x 2 m) for 8 weeks and then housed in groups of 8 in straw-bedded pens (5 x 8 m). According to the results of the analysis, the contributions from all calves to global warming potential, acidification potential, eutrophication potential, non-renewable energy use was high. In particular, the impact generated from global warm potential was 7 kg CO2 – eq per day, and the impact of non-renewable energy use was 38 MJ – eq per day. Our results estimated for the first time the environmental impact generated from buffalo calves. We conclude that the strategies to mitigate the effects on the environment impact must start from the birth of the buffalo calves and then continue throughout its life cycle.